ATTEMPT TO BUILD A QUANTITATIVE MODEL FOR PREDICTING FINANCIAL FAILURE OF A SAMPLE OF ALGERIAN ECONOMIC INSTITUTIONS - Bouzerba Rachid (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to attempt to formulate a quantitative model with the capability to provide early prediction of the financial status of an economic institution, whether it is heading towards financial failure or in a sound financial position, through the composition of a combination of financial ratios that have the ability to discriminate between successful institutions and failing institutions. This was conducted using the Multiple Discriminant Analysis (MDA) method, which was applied to a sample consisting of 32 industrial institutions, of which 20 were successful institutions and 12 were failing institutions according to the criterion of consecutive losses for more than two years.The study concluded that three (03) ratios out of twenty-eight (28) financial ratios have the ability to discriminate between successful institutions and failing institutions according to the discriminant analysis model, which achieved a classification accuracy of 96.9%.